The Alert and Creative Entrepreneur: A Clarification - Israel M. Kirzner (Research Institute of Industrial Economics (IFN), 2008)
Israel M. Kirzner is the 2006 winner of The International Award for Entrepreneurship and Small Business Research (the FSF-Nutek Award). In this Prize Lecture he argues that a number of those who have commented on his work have misunderstood certain aspects of his theoretical system, and as a result the common distinction in the literature between Schumpeterian and Kirznerian entrepreneurs is flawed. He also argues that his understanding of the market process (set in motion by entrepreneurial decisions) provides a theoretical underpinning for public policy vis-à-vis entrepreneurship. Professor Kirzners main contributions to the economics of entrepreneurship were also presented and evaluated by Douhan, Eliasson and Henrekson (2007).
Keywords: B49; B52; B53; O31; 330; Austrian economics; Economic development; Entrepreneurship; Small business economics; Entrepreneurship-Ansatz; Kreativität; Unternehmenserfolg; KMU